Spatial view on the development strategy of the southern islands, case study: Hengam island - Mohammad Shafie; Reza Sameh (مهندسی و مدیریت ساخت, 2022)
Geographical factors and elements, specifically geographic regions, play a role in political, economic, and social events and processes. One of these geographical regions is the Middle East, which plays an important role in world events. Iran is known as the most important country in the Persian Gulf and as one of the main and key players in important regional energy events. Therefore, it can be argued that in addition to geopolitical credibility, Iran also has unique value and capabilities in the field of geo-economics. On the other hand, Iran is important due to its transit position, which is due to its geopolitical advantages, i.e. being located at four international roads. This crossroads connects Africa to Asia and Asia to Europe. The main feature of the Persian Gulf is its set of islands, which has given it a multifaceted role. The current article studies the regional importance of the Persian Gulf and Iranian islands, in this regard, it first examines their regional and geographical characteristics and then deals with their regional and cultural characteristics, then focusing on the current natural and social characteristics of the island. Finally, according to its territorial capabilities and geopolitical and geographical talents, the areas of development and capabilities of the island in this direction have been stated.